Strategi Pembelajaran Afektif Guru PAI dalam Menanggulangi Kenakalan Siswa di SMK Brawijaya Kepung Kediri - Dhuha, Ghofur (Ali Muchasan, 2015)
In education, student misbehavior is a phenomenon that is always interesting to discuss. Hence the need for directional guidance for students as the next generation, so that they can meet the expectations of the aspired. Islamic Education teacher was instrumental to overcome various problems of juvenile delinquency that occurred in students, so that the young generation in the future better and not easily fall into actions that harm himself. The study, the researchers did was kind of qualitative descriptive study. This approach in the implementation of the research do occur naturally, it is, in normal situations that are not manipulated circumstances and conditions, emphasizing on description naturally. Besides, the authors collected data using the method of observation, interviews and documentation. The stages of research include: orientation, data collection phase (field), the data collection phase. Data analysis includes qualitative descriptive analysis technique, so that the results of this research produces more data written or oral from people's behavior and observed.